Analisis Kebutuhan Media Audiovisual Pada Mata Pelajaran Pendidikan Pancasila Untuk Siswa SMP - Suswiti Suswiti; Yusuf Hartono; L.R. Retno Susanti (STKIP Singkawang, 2006)
This study aims to analyze the need for the use of audiovisual media in Pancasila Education learning at the Junior High School (SMP) level. This research is motivated by the low interest and understanding of students towards Pancasila material which is still dominated by conventional learning methods. The study used a quantitative descriptive approach with data collection through questionnaires distributed to 30 junior high school students. The research instrument covered four aspects of audiovisual media needs, namely pedagogical, technical, cognitive, and aesthetic. The results showed that 75% of students stated that role-playing helped understand the values of the Pancasila Student Profile, 73% considered video media effective in improving critical thinking skills, and 81% of students preferred video media that were interesting and easy to access. Meanwhile, 67% of students stated that technological facilities at school were sufficient to support learning, and 78% of students expected audiovisual media to be equipped with direct feedback. The novelty of this study lies in mapping the needs of role-playing-based audiovisual media according to the characteristics of junior high school students as a basis for developing Pancasila Education media oriented towards strengthening the Pancasila Student Profile. The findings of this study provide empirical contributions for teachers and media developers in designing more effective, contextual, and meaningful Pancasila Education learning.